ANALISIS FAKTOR - FAKTOR YANG MEMPENGARUHI PREDIKSI PERINGKAT OBLIGASI PADA PERUSAHAAN MANUFAKTUR YANG TERDAFTAR DI BURSA EFEK INDONESIA - Ria Rizki Eka Santi, 12.05.52.0104; Nuswandari, Cahyani (Students' Journal of Accounting and Banking, 2016)
This study has the objective to analyze empirically effect of accounting factor (productivity, leverage, profitability, liquidity, and growth), and the non-accounting factor (auditor reputation) on prediction the bonds level. Population in this research is the entire bond of manufacture companies listed in Indonesian Stock Exchange and registered in bond ratings issued by PT. PEFINDO within period 2008-2014. The sampel in this research used purposive sampling technique which consist of 57companies. The analysis was performed by logistic regression. Hypothesis testing results show that Profitability and Auditor Reputation effect to Prediction The Bond Level, while Productivity, Leverage, Likuidity and Growth has no effect on Prediction the Bond Level.Keywords: Prediction The Bond Level, Productivity, Leverage, Profitability, Liquidity, Growth, Auditor Reputation